The Verbal Abuse in Virtual Spaces Among University Students: Reconstruction of Communication Ethics from the Perspective of Islamic Education - Novia Nasyomia; Rizky Dwi Pradana (Amorti: Jurnal Studi Islam Interdisipliner, 2026)
This article explores the issue of verbal abuse within students’ virtual interactions from the standpoint of Islamic educational ethics. The increasing use of virtual communication platforms, particularly WhatsApp, has reshaped the way university students engage in academic and social communication. Despite offering efficiency and accessibility, virtual interaction also creates ethical vulnerabilities, including the emergence of ridicule, degrading remarks, offensive expressions, and other forms of verbal aggression in online conversations. This study adopts a qualitative library research design employing normative and thematic interpretative approaches. The data were obtained from Qur’anic verses, contemporary tafsir literature, academic books, and previous studies concerning virtual communication, cyber interaction, and Islamic education. The analysis was conducted using content analysis by synthesizing perspectives from communication theory, the online disinhibition effect, and Islamic ethical principles. The study reveals that verbal aggression in students’ virtual spaces is influenced by the weakening of social restraint in online environments, the text-oriented nature of digital communication, and insufficient ethical awareness in media engagement. From the perspective of Islamic education, QS. Al-Ḥujurāt verse 11 emphasizes the prohibition of mockery, humiliation, and derogatory labeling because such behavior undermines human dignity and social harmony. Contemporary interpretations proposed by Wahbah al-Zuhaili, Muhammad al-Tahir Ibn Ashur, and Sayyid Qutb demonstrate that Islamic communication ethics remain highly relevant in responding to verbal misconduct within contemporary virtual environments. This study highlights the importance of integrating digital literacy with moral and character education to encourage a more respectful, ethical, and civilized academic communication culture.